2022
DOI: 10.3389/fgene.2022.900713
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Necroptosis-Related Prognostic Signature to Reveal Immune Infiltration and Predict Drug Sensitivity in Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is a common type of primary liver cancer and has a poor prognosis. In recent times, necroptosis has been reported to be involved in the progression of multiple cancers. However, the role of necroptosis in HCC prognosis remains elusive.Methods: The RNA-seq data and clinical information of HCC patients were downloaded from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases. Differentially expressed genes (DEGs) and prognosis-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…identified frequent amplification of USP21 (22%) in human pancreatic ductal adenocarcinoma, and USP21 deubiquitinase promoted pancreatic cancer cell stemness via Wnt pathway activation [ 36 ]. Although there have been studies on hepatocellular carcinoma necrosis genes, validation by PCR alone is not sufficient [ 37 ]. In the present study, we observed high expression of HSP90AA1, PPIA, SQSTM1, and USP21 in HCC tissues by immunohistochemistry experiments, which indirectly validated the value of the necroptosis-related signature in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…identified frequent amplification of USP21 (22%) in human pancreatic ductal adenocarcinoma, and USP21 deubiquitinase promoted pancreatic cancer cell stemness via Wnt pathway activation [ 36 ]. Although there have been studies on hepatocellular carcinoma necrosis genes, validation by PCR alone is not sufficient [ 37 ]. In the present study, we observed high expression of HSP90AA1, PPIA, SQSTM1, and USP21 in HCC tissues by immunohistochemistry experiments, which indirectly validated the value of the necroptosis-related signature in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhao et al analyzed the prognostic values of necroptosis-associated lncRNA in stomach cancer [ 38 ]. Ren et al constructed a 13-NRG signature for predicting HCC prognosis using univariate cox and lasso cox regression analyses [ 39 ]. However, these prognostic signatures were established only through analysis of public databases and lacked validation in clinical cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…However, gemcitabine, selumetinib, and sorafenib possessed higher IC50 values in the low-risk group. The lower the IC50 value, the more effective the treatment of drugs [ 51 ]. A nomogram integrates the effects of predictors on the outcomes and allows clinicians to predict patient survival by evaluating the whole effect [ 52 ].…”
Section: Discussionmentioning
confidence: 99%